Analisis SWOT untuk Meningkatkan Kepuasan Konsumen di Babe Gym Bandar Lampung - Nurbari, Fiqih Alpriansyah; Wicoko, Adistyo; Riyanto, Adi; Agung, Iqbal Sobri Permana; Sanjaya, Vicky F (JURNAL MANAJEMEN DAN BISNIS, 2025)
Increasing public awareness of the importance of a healthy lifestyle encourages the growth of the fitness industry in Indonesia, including in the city of Bandar Lampung. Babe Gym is one of the business actors in this field that needs to formulate a strategy to maintain and increase customer satisfaction in the midst of fierce competition. This study aims to analyze internal and external factors that affect Babe Gym's customer satisfaction using a SWOT analysis approach. The research was conducted through a qualitative approach with observation methods, in-depth interviews, and the distribution of questionnaires to management and customers. Data analysis is carried out using IFE and EFE Matrices to identify strengths, weaknesses, opportunities, and threat factors, which are then incorporated into the SWOT Matrix to formulate the right development strategy. The results of the study show that Babe Gym has strength in terms of affordable price and the owner's commitment to customer comfort. However, the disadvantages include a less strategic location, lack of promotion, and limited facilities. The main opportunities come from the increasing public interest in healthy lifestyles and the potential for cooperation with supplement business partners. The threats faced are low customer loyalty and a lack of focus on service and equipment safety. Babe Gym's strategic position is in Quadrant I (Grow and Build), which recommends an aggressive strategy for expansion and service improvement. The strategy includes improving facilities, external cooperation, and strengthening promotions and customer loyalty. This research provides a strategic basis for the development of competitive and sustainable fitness services.